Annotated Corpus for Sentiment Analysis in the Uzbek Language (Uzbekistan Open Conference, 2025)
This study examines the methodology for creating an annotated corpus for sentiment analysis in the Uzbek language. Unlike high-resource languages with large annotated corpora, resources for the Uzbek language remain limited. The study analyzes international experience and proposes a methodology for developing a corpus adapted to the linguistic characteristics of the Uzbek language. The proposed approach contributes to the development of more accurate and reliable sentiment analysis models for Uzbek.